Application of Quantum Learning Education Model Through Contextual Approaches For Alpha Generations In Elementary School Children - Rizky Maydika Sampoerna; Nuril Af’idah; Niyyah Daniyatul Millah; Pita Nursiana (International Consortium of Education and Culture Research Studies, 2020)
Alpha generation is the generation born between the years 2010-2024. Alpha generation is very vulnerable to the negative effects of digital influence if it is not matched by character education from an early age, because the rapid development of technology is more inherent in the era of alpha generation than the previous generation which enabled the lifestyle of the alpha generation to be strongly influenced by technological developments. In the sphere of education, the alpha generation is able to develop through a media search for references that are not only in the form of books, but can be obtained from journals, ebooks, internet sites and so on. With the rapid development of technology which also has an impact on the scope of alpha generation education, the author provides an innovative educational method for the alpha generation, namely